2011
DOI: 10.1007/s00436-011-2611-1
|View full text |Cite
|
Sign up to set email alerts
|

Antiplasmodial activity of Xanthium strumarium against Plasmodium berghei-infected BALB/c mice

Abstract: The present work was undertaken to evaluate the antiplasmodial activity of ethanolic leaves extract of traditional medicinal plant Xanthium strumarium in Plasmodium berghei-infected BALB/c mice along with phytochemical screening and acute toxicity test to support its traditional medicinal use as a malaria remedy. The ethanolic leaves extract of X. strumarium (ELEXS) 150, 250, 350 and 500 mg/kg/day demonstrated dose-dependent chemosuppression during early and established infection long with significant (p < 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 16 publications
(14 reference statements)
4
48
1
Order By: Relevance
“…Plasmodium berghei (NK-65) is a lethal rodent malaria parasite. Mice infected with parasite die within 7-10 d of infection in normal course of infection (Chandel & Bagai, 2010). In the present study, in vitro results showed that AREBA is effective at high dose, while in vivo results showed that it is effective only when administered at lower concentration.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…Plasmodium berghei (NK-65) is a lethal rodent malaria parasite. Mice infected with parasite die within 7-10 d of infection in normal course of infection (Chandel & Bagai, 2010). In the present study, in vitro results showed that AREBA is effective at high dose, while in vivo results showed that it is effective only when administered at lower concentration.…”
Section: Discussionsupporting
confidence: 44%
“…Natural products, mainly plants, are fundamental source of numerous drugs and therapeutics. Interestingly, the most important and effective drugs used in malaria treatment have been derived from the plants (Chandel et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The herb has also been credited for its astringent, febrifugal, stimulant, tonic, and diuretic properties [1] . The previous pharmacological investigations on A. bracteosa have reported the antifeedant activity against Spodoptera littoralis larvae [2] , cancer chemopreventive [3] , and antiplasmodial [4,5] activities. A. bracteosa was also reported to inhibit the acetylcholinesterase, butyrylcholinesterase and lipoxygenase activity [6] .…”
Section: Introductionmentioning
confidence: 99%
“…It is a perennial erect or ascending hairy herb, often prostrate with oblanceolate or sub-spathulate leaves and grows up to 5-50 cm tall. It is distributed in subtropical and temperate regions from Kashmir to Bhutan, Pakistan, Afghanistan, China, Malaysia, western Himalayas, plains of Punjab and upper gangetic plains of India (Khare, 2007) at an altitude of 1300 m. In India, it abounds in western Himalaya at an altitude of 1300 m (Chandel and Bagai, 2010). It is found along roadsides, open slopes and rock cervices up to 1500 m above mean sea level (Chauhan, 1999 However, the aim of present study is to check the antidiabetic potency of the hydroalcoholic extract of leaves of Ajuga bracteosa in the form of hypoglycemic value in Alloxan induced diabetic chicks.…”
mentioning
confidence: 99%